2012
DOI: 10.1186/1471-2229-12-51
|View full text |Cite
|
Sign up to set email alerts
|

Atypical DNA methylation of genes encoding cysteine-rich peptides in Arabidopsis thaliana

Abstract: BackgroundIn plants, transposons and non-protein-coding repeats are epigenetically silenced by CG and non-CG methylation. This pattern of methylation is mediated in part by small RNAs and two specialized RNA polymerases, termed Pol IV and Pol V, in a process called RNA-directed DNA methylation. By contrast, many protein-coding genes transcribed by Pol II contain in their gene bodies exclusively CG methylation that is independent of small RNAs and Pol IV/Pol V activities. It is unclear how the different methyla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…Interestingly, in the latter, more than half of the highly methylated genes that are differentially expressed are targeted by small RNAs (for example, Fig. 3e), suggesting that RdDM may have a role in the regulation of transcription of a subset of genes in diatoms, as recently inferred from studies of the atypical DNA methylation on some genes in A. thaliana 43 . Furthermore, we observed that the captured exon found in the R59 repeat is inserted in reverse orientation with respect to the PiggyBac backbone ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Interestingly, in the latter, more than half of the highly methylated genes that are differentially expressed are targeted by small RNAs (for example, Fig. 3e), suggesting that RdDM may have a role in the regulation of transcription of a subset of genes in diatoms, as recently inferred from studies of the atypical DNA methylation on some genes in A. thaliana 43 . Furthermore, we observed that the captured exon found in the R59 repeat is inserted in reverse orientation with respect to the PiggyBac backbone ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 97%
“…Plant genes, including those with presumed or demonstrated biological functions, can have methylation patterns that resemble TEs (You et al, 2012; Zemach et al, 2010a), and may therefore be regulated more like TEs than conventional genes. TEs are generally highly methylated at CG sites (Figure 6A, left panel), whereas most Arabidopsis genes have lower methylation levels, except for a distinct group that resembles TEs (Figure 6A).…”
Section: Resultsmentioning
confidence: 99%
“…We propose that this enrichment might compensate the deprivation of maintenance DNA methyltransferases MET1 and CMT3 during female gametogenesis. In contrast with the egg cell, the central cell and the synergid cells expressed low levels of de novo DNA methyltransferases and undetectable levels of maintenance DNA methyltransferases, which likely explains why these cells express genes that are silenced by DNA methylation in vegetative tissues [14,[17][18][19].…”
Section: Resultsmentioning
confidence: 99%